Social, Economic, Environmental Benefits of Rural People from Handicraft Products in Some Villages – Menoufia Governorate - Elbasha, Hossam Hafiz; Gad, Moammer Gaber; Abdel-Aziz, Basyouny Embaby (Journal of agricultural, environmental and veterinary sciences, 2022)
This search amid mainly identify the most important Handicraft Products in study area and reasons of selecting this product, to determining level of social, economic, environmental benefit of Rural People from Handicraft Products, variables affecting the benefit level, problems facing producers and suggestions for solving these problems. Data were collected from 200 producers in 8 villages belonging to 4 districts. "Person correlation coefficient and Multiple-regression were used for data analyzing. The study revealed the following results: - Textile hand-made, chairs and baskets, carpets, colored glass, covers, matrixes, jars and pottery, were the most crafits producing by rural people - The most important reasons to select Handicraft Products are: a means of subsistence, helping families, and providing new job opportunities for young people. - The most important variable which affects the benefit level of Handicraft Products was the satisfaction of producers regarding these industries. - The Main problems facing producers were high price of electricity, marketing problems, and the large amount of taxes.